2021
DOI: 10.47278/journal.ijvs/2021.064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bali Cattle Semen Quality During Cryopreservation with Coconut Water-Based Extenders

Abstract: The aim of this research was to evaluate the Bali cattle semen quality during cryopreservation with different types of extenders in term of live, total motility, progressive motility, and abnormality of post-thawed bull sperms. The treatments were AndroMed® (T0), Tris-based egg yolk diluent (T1), Tris-based coconut water diluent (T2), Coconut water egg yolk diluent (T3). Bulls’ semen was collected from two adult Bali cattle maintained at the semen production facility at Bali Artificial Insemination Center, Tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Another study showed that GTE contains catechins, epi catechins, gallocatechin, epigallocatechin, gallocatechin gallate, and Epigalocathecin gallate (EGCG). EGCG is the most promising bioactive compound due to its strong antioxidant activity [ 19 ], in turn improving sperm motility, and viability, and increase fertility [ 20 , 21 ]. EGCG is a kind of catechin that makes up 13% of the total polyphenols in GTE and can only be found naturally in GTE, while other types of catechins can only be found in fruits and vegetables [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that GTE contains catechins, epi catechins, gallocatechin, epigallocatechin, gallocatechin gallate, and Epigalocathecin gallate (EGCG). EGCG is the most promising bioactive compound due to its strong antioxidant activity [ 19 ], in turn improving sperm motility, and viability, and increase fertility [ 20 , 21 ]. EGCG is a kind of catechin that makes up 13% of the total polyphenols in GTE and can only be found naturally in GTE, while other types of catechins can only be found in fruits and vegetables [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the validity and reliability of inbreeding (IB) results obtained with sexing through the 5-10% BSA column, molecular verification needs to be conducted using the duplex PCR method. The applications of IB combined with spermatozoa sexing in several regions of Indonesia have achieved a sex match rate of 76-89% in field calves (Gunawan et al 2015;Sawitri et al 2021). Therefore, this study aims to molecularly verify sexing results of spermatozoa carrying X and Y chromosomes using the PCR method.…”
Section: Introductionmentioning
confidence: 99%
“…
T he inability of national meat production in Indonesia has resulted in the government still importing beef from several countries. Of course, this indicates that beef production still needs to be put up to target (Sawitri et al, 2021). Efforts can be made to improve the livestock system in Indonesia, especially to achieve the target of one-year birth intervals or to shorten the calving-conception interval by detecting early pregnancy in cows after mating (Kaya et al, 2016).
…”
mentioning
confidence: 99%